Variability in forms of organisation in biotechnology firms - Terttu Luukkonen (The Research Institute of the Finnish Economy (ETLA), 2003)
This paper examines variability in forms of organisation, in terms of forward and backward networking versus vertical integration, in biotechnology SMEs. The study examines forms of organisation in a set of firms across different application segments. The forms of organisation vary by application segment in biotechnology, but differences are not clear-cut, and a firm can apply different forms to different application segments in its activities. Reasons for the variability are related to the stringency of the regulatory approval systems, technological risks, and the costs needed for building up full-scale manufacturing facilities thus influencing the choices of forms of organisation through the need for and access to funding. The paper will finally discuss the notion of networking as a separate form of organisation of economic activity and the extent of its applicability to biotechnology.
Keywords: 330; Biotechnology industry; network firm; organisational form; Biotechnische Industrie; Organisationsstruktur